Increased visceral sensitivity, elevated anxiety, and depression levels in patients with functional esophageal disorders and non‐erosive reflux disease. Issue 9 (14th June 2021) - Losa, Marco; Manz, Salomon M.; Schindler, Valeria; Savarino, Edoardo; Pohl, Daniel
Abstract: Background: Little is known about possible underlying psychological abnormalities and physiology of reflux hypersensitivity (RH) as defined in the recent Rome IV classification. We aimed to assess markers of psychological comorbidity as well as gastro‐esophageal reflux measurements in RH patients compared to controls and also in patients with functional heartburn (FH) and non‐erosive reflux disease (NERD) versus controls. Methods: Data of 304 patients visiting our Functional Diagnostics Centre from 2016 to 2018 were analyzed. We focused on a psychological assessment using validated questionnaires (visceral sensitivity index; VSI, hospital anxiety and depression score; HADS) as well as multichannel intraluminal impedance (MII) and pH‐metry data from the diagnostic work‐up. Key Results: We found a decreased VSI of 57.8 ± 15.4 points (pts) among RH patients (n = 45) indicating higher visceral sensitivity compared to 85.7 ± 2.0 pts in the control group (n = 31, P < 0.001). Furthermore, a significant difference in VSI was found between the FH (60.8 ± 23.3 pts, n = 59, P < 0.001) and between the NERD (61.9 ± 20.8 pts, n = 67, P < 0.001) both compared to the control group. The HADS also displayed a significant difference between the RH (11.9 ± 6.0 pts, P < 0.001), FH (11.0 ± 7.4 pts, P < 0.001), respectively, NERD (11.3 ± 8.9 pts, P < 0.001) as compared to the control group (2.0 ± 1.4 pts). Conclusions and Inferences: Increased sensation to visceral stimuli as well as anxiety and depression appears to play an important role not only in reflux hypersensitivity and functional heartburn as defined by Rome IV but also in NERD. These findings are in line with the disease concept of disorders of gut‐brain interaction in which psychological comorbidities and visceral hypersensitivity play a major role. Abstract : In this study, Losa/Manz et al. investigated whether visceral sensitivity, anxiety, and depression levels are altered in patients with non‐erosive reflux disease as well as in patients with functional esophageal disorders, namely reflux hypersensitivity and functional heartburn, as compared to healthy volunteers. The findings presented here are in line with the disease concept of disorders of gut‐brain interaction in which psychological comorbidities and visceral hypersensitivity play a major role.